Peran Pendidik Kristen Mengatasi Kemerosotan Moral di Era Digital - Chrismas Febe Wulandari (Journal on Education, 2023)
The development of the era in the digital era is a big challenge for students. There are many changes that occur not only in technology but in the way people view life. Great influence is very risky to clash with spiritual values. This problem will be a threat if educators are not optimal in trying to learn. Christian Religious Education teachers must carry out their role to make people become disciples of the Lord Jesus Christ. Through the qualitative method of literature study, it can be concluded that teachers as educators to overcome moral decline in this digital era must be a priority for teachers and parents to work together in suppressing the moral decline that occurs. So teachers must know the challenges in the digital era so that they can provide solutions for students. Teachers must teach Christian ethical values in the perspective of the Bible as the foundation of life that is taught and applied in everyday life. As well as Christian